Weed Control in Cucurbit Crops (Muskmelon, Cucumber, Squash, and Watermelon) - William M. Stall (EDIS, 2008)
Revised! HS-190, a 6-page fact sheet by William M. Stall, describes recommended weed control methods for Florida producers, describing crop competition, mechanical control, mulching, and herbicides. Includes a table of chemical weed controls for cucurbit crops in Florida. Published by the UF Department of Agronomy, November 2007.